Primary Osteoma Cutis in the Interscapular Region of a Dog. (January 2019) - Woo, S.-H.; Go, D.-M.; Lee, S.-H.; Han, S.-S.; Kim, D.-Y.
Summary: A 9-year-old neutered male Shih Tzu was presented with three contiguous firm nodules in the subcutaneous tissue of the interscapular region. Histopathological examination revealed that the nodules consisted of mature lamellar bone with a Haversian system, with no apparent lesion around the bone. Clinical examination revealed that the dog had no underlying disease and no history of trauma at the lesion site. Based on these findings and on the medical history, a diagnosis of primary osteoma cutis was made. Osteoma cutis is rare in both human and veterinary medicine, and most dogs reported to have secondary osteoma cutis. To our knowledge, this case is only the second report of primary osteoma cutis in a dog.